Uncovering hidden β-adrenergic agonist exposure from meat consumption through nationally representative human biomonitoring in Taiwan - Ho-Tang Liao; Tzu-Hsuan Peng; Chien-Jen Wang; Jing-Fang Hsu; Ching-Chun Lin; Wen-Harn Pan; Shu-Lih Chia; Pau-Chung Chen (International Journal of Hygiene and Environmental Health, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

High-performance hybrid supercapacitors based on MXene/SnS2/CNT composites on nickel foam electrodes - Chii-Rong Yang; Yang-Yi Lin; Ching-Tang Lin; Shih-Feng Tseng (Chemical Engineering Journal, 2025)

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

The herbicide 2,4-dichlorophenoxyacetic acid induces pancreatic β-cell death via oxidative stress-activated AMPKα signal downstream-regulated apoptotic pathway - Ken-An Lin; Chin-Chuan Su; Kuan-I Lee; Shing-Hwa Liu; Kai-Min Fang; Chih-Hsin Tang; Wei-Cheng Lia; Chun-Ying Kuo; Kai-Chih Chang; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology Letters, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Catalytic adsorption and decomposition of per(fluorinated) compounds using zeolites for greenhouse gas mitigation - Ndumiso Vukile Mdlovu; Kuen-Song Lin; Cheng-Yan Tang; Ching-Yen Chang; Abrar Hussain; Jamshid Hussain (Chemosphere, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Changes in Trace Elements During Early Stages of Chronic Kidney Disease in Type 2 Diabetic Patients - Ching-Chiang Lin; Ching-Tang Shih; Chien-Hung Lee; Yeou-Lih Huang (Biological Trace Element Research, 2018)

The Divalent Elements Changes in Early Stages of Chronic Kidney Disease - Wan-Ju Kung; Ching-Tang Shih; Chien-Hung Lee; Ching-Chiang Lin (Biological Trace Element Research, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Prevalence of potential nitrogen‐fixing, green sulfur bacteria in the skeleton of reef‐building coral I sopora palifera - Shan‐Hua Yang; Sonny T. M. Lee; Chang‐Rung Huang; Ching‐Hung Tseng; Pei‐Wen Chiang; Chung‐Pin Chen; Hsing‐Ju Chen; Sen‐Lin Tang (Limnology and Oceanography, 2016)
Microbial endoliths, which inhabit interior pores of rocks, skeletons and coral, are ubiquitous in terrestrial and marine environments. In this study, various colored layers stratified the endolithic environment within the skeleton of Isopora palifera ; however, there was a distinct green‐pigmented layer in the skeleton (beneath the living coral tissue). To characterize diversity of endolithic microorganisms, 16S ribosomal RNA gene amplicon pyrosequencing was used to investigate bacterial communities in the green layer of eight I. palifera coral colonies retrieved from two locations on Green Island, Taiwan. The dominant bacterial group in the green layer belonged to the bacterial phylum Chlorobi, green sulfur bacteria capable of anoxygenic photosynthesis and nitrogen fixation. Specifically, bacteria of the genus Prosthecochloris were dominant in this green layer. To our knowledge, this is the first study to provide a detailed profile of endolithic bacteria in coral and to determine the prevalence of Prosthecochloris in the green layer. Based on our findings, we infer that these bacteria may have an important functional role in the coral holobiont in the nutrient‐limited coral reef ecosystem.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Application of a Sustainable Fisheries Development Indicator System (SFDIS) for Better Management Outcomes in Taiwan Offshore and Coastal Fishery - Wen-Hong Liu; Kun-Lung Lin; Hao-Tang Jhan; Ta-Ly Lin; De-Lu Ding; Ching-Hsien Ho (Coastal Management, 2011)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Ploidy doubling by in vitro culture of excised protocorms or protocorm-like bodies in Phalaenopsis species - Wen Huei Chen; Ching Yan Tang; Yu Lin Kao (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)